2021
DOI: 10.1007/s41365-021-00977-w
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion behavior between Cr and Zr and its effect on the microcracking behavior in the Cr-coated Zr-4 alloy

Abstract: High-temperature chromium (Cr)-zirconium (Zr) interdiffusion commonly occurs in Cr-coated zircaloys applied for enhanced accident-tolerant fuel (ATF) claddings. Such interdiffusion changes the interfacial microstructure and thus the fracture mechanism of the coating under external loading. In this study, the interdiffusion behavior in a magnetron sputtered Cr coating deposited on a Zr-4 alloy was studied in a vacuum environment at 1160 °C. In addition, the effect of interdiffusion on the microcracking behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Because of the intermediate diffusion layer's formation, the Zr-4 substrate has excellent adhesion to Cr coating, which will form various intermediate phases but will not affect the substrate and coating's bonding state. [3]. Furthermore, the Cr coating can provide a dense Cr 2 O 3 protective film in a water vapor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the intermediate diffusion layer's formation, the Zr-4 substrate has excellent adhesion to Cr coating, which will form various intermediate phases but will not affect the substrate and coating's bonding state. [3]. Furthermore, the Cr coating can provide a dense Cr 2 O 3 protective film in a water vapor environment.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of temperature, many studies demonstrated that the phenomenon of structural and composition change in Cr-coated Zr-4 was found at high temperatures, such as phase transition in the substrate, element interdiffusion [20,21], grain coarsening, and void and intermetallic layer generations [22]. Huang et al [23] indicated that the microstructure of the Zr-4 alloy substrate changed via recrystallization at high temperatures, and an intermetallic layer of Cr 2 Zr was formed.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [23] indicated that the microstructure of the Zr-4 alloy substrate changed via recrystallization at high temperatures, and an intermetallic layer of Cr 2 Zr was formed. Jiang et al [20,24] indicated that high temperatures caused the crystallizing morphology of the Cr coating to change from columnar grains to equiaxial grains. Simultaneously, grain coarsening and a brittle intermetallic ZrCr 2 layer formed at the interface, which easily cracked under stress.…”
Section: Introductionmentioning
confidence: 99%